Trasversal territories. Rural and industrial small towns in Sicily and Spain - Guido Cimadomo; Renzo Lecardane; María Isabel Alba Dorado (Agathón)
The orographic and natural conditions, together with small towns’ cultural, heritage and industrial conditions, have become the landscape of relationships between spaces where silence, slowing down and acceleration define the urban and human imaginary of these transversal territories. Although very different from each other in terms of topographical location, traditions and cultural and linguistic specificities, it is possible to find constants of criticality and potential. This essay illustrates new readings and settles meanings to initiate a collaborative work in Sicily and Spain along the Trasversale Sicula and in the mining landscape of the Minas de La Reunión in the province of Seville. Here, it is possible to combine material and immaterial imaginaries that find the ideal setting in the rural and industrial small towns to start again from what remains and from the potential given by the generations in comparison.